Pain Location Is Associated with Fracture Type in Acute Osteoporotic Thoracolumbar Vertebral Fracture: A Prospective Observational Study. Issue 2 (28th July 2021) - Zhang, Haiping; Yang, Bo; Hao, Dingjun; Wang, Biao; He, Baorong; Sun, Honghui; Li, Hui; Zhang, Xuefang
Abstract: Objective: This study investigated the relationship between pain location and fracture type in patients with acute osteoporotic vertebral fracture (OVF). Design: A prospective observational study. Subject: A total of 306 patients with acute OVF were included. Methods: The site of pain of each patient was recorded, and the patients were divided into a group with pain at the fracture site (group 1) and a group with pain at a non-fracture site (group 2). Fractures were classified into four types: type I, upper endplate type; type II, central type; type III, lower endplate type; and type IV, burst type. Results: There were 146 patients in group 1, of whom 20.55% (30/146) had type I fractures, 33.56% (49/146) had type II fractures, 15.75% (23/146) had type III fractures, and 30.14% (44/146) had type IV fractures. There were 227 patients in group 2, of whom 57.27% (130/227) had type I fractures, 5.29% (12/227) had type II fractures, 35.24% (80/227) had type III fractures, and 2.20% (5/227) had type IV fractures. There was a statistical difference in the fracture type distribution between the two groups ( P  < 0.05). The visual analog scale score in group 1 was higher than that in group 2 at the initial diagnosis ( P  < 0.05). Conclusions: For patients with acute OVF, the site of pain is related to the type of fracture. The pain at the fracture site is more often observed in the central type and burst type of fractures, whereas pain at a non-fracture site is more often observed in the upper and lower endplate types of fractures. Additionally, when OVF is suspected, radiological assessment of the thoracic and lumbar spine is recommended to better detect fractures that could cause pain distal to the site of the fracture.